Use of Grafts on an Open Gap Is Advantageous for Preventing Correction Loss in 1-Week Staged Bilateral Open-Wedge High Tibial Osteotomies - Yoon, Kyoung Ho; Song, Sang Jun; Hwang, Sung Hyun; Jung, Cheol Hyun; Park, Cheol Hee (The Journal of Knee Surgery, 2022)
One-week staged bilateral open-wedge high tibial osteotomies (OWHTOs) can be a safe procedure, with the added advantage of fast functional recovery, cost saving, and reduced hospital stay. However, there can be concerns about correction loss after 1-week staged OWHTOs because high loading is inevitably applied to osteotomy sites during postoperative weight bearing. Although leaving the osteotomy site with no grafts is possible in OWHTOs, the use of grafts can provide additional stability to the osteotomy site and prevent correction loss. We compared the amount and incidence of correction loss between 1-week staged bilateral OWHTOs with and without allogenic bone grafts. Seventy-five patients who underwent 1-week staged bilateral OWHTOs with a locking spacer plate (Nowmedipia, Seoul, Korea) by a single surgeon were retrospectively reviewed. Allogenic cancellous bone grafts were applied in 53 patients (group G; 106 knees, operated consecutively between 2012 and 2017) but not in 22 patients (group N; 44 knees, operated consecutively between 2017 and 2019). Demographics were similar between the groups. Radiographically, the mechanical axis (MA), medial proximal tibial angle (MPTA), and posterior tibial slope (PTS) were evaluated preoperatively and within 1 year postoperatively. Unstable hinge fracture was investigated using computed tomography in all cases. The incidence of correction loss (MPTA loss ≥ 3 degrees) was determined. There were no significant differences in the MA, MPTA, and PTS between the groups preoperatively and 2 weeks postoperatively. The incidence of unstable hinge fractures did not differ. The losses in MA, MPTA, and PTS during the first postoperative year were significantly greater in group N than in group G (MA, −5.5 vs. −2.3 degrees; MPTA, −3.0 vs. 0 degrees; PTS, −2.0 vs. −0.7 degrees; p < 0.05 on all parameters). The correction loss incidence was 6.6% (7/106) and 31.8% (14/44) in groups G and N, respectively (p < 0.001). Appropriate treatment is necessary to prevent correction loss in 1-week staged bilateral OWHTOs. Grafting, which provides additional stability to the osteotomy site, is a recommended method. Level of evidence is IV.
Keywords: knee; high tibial osteotomy; open-wedge; staged; correction loss